Systematic review and meta-analysis for the proximal junctional kyphosis in adolescent idiopathic scoliosis - Zhao, Jian; Huang, Chen; Liu, Yifei; Liu, Da; Liao, Dongfa (Frontiers in Pediatrics, 2024)
The risk factors of PJK (proximal junctional kyphosis) related to AIS(adolescent idiopathic scoliosis) are inconsistent due to heterogeneity in study design, diagnostic criteria, and population. Therefore, the meta-analysis was conducted to investigate the factors affecting PJK after posterior spinal fusion for AIS patients.We implemented a systematic search to obtain potential literature relevant to PJK in AIS surgery. Then, a meta-analysis was performed to assess the incidence of PJK and its risk factors.We retrieved 542 articles, and 24 articles were included. The PJK incidence was 17.67%.The use of hooks at UIV (upper instrumented vertebrae) (p=0.001) could prevent PJK. Before surgery, the larger TK (thoracic kyphosis) (p<0.001), GTK (global thoracic kyphosis) (p<0.001), and LL (lumbar lordosis) (p<0.001) were presented in the PJK group. Immediately post-operatively, in the PJK group, the following parameters were higher: TK (p=0.001), GTK(p<0.001), LL (p=0.04), PJA (proximal junctional angle) (p<0.001), and PJA-RCA (rod contouring angle) (p=0.001). At the final follow-up, the following parameters were higher in the PJK group: TK (p<0.001), GTK(p<0.001), LL(P<0.001), and PJA (P<0.001). Sub-group analysis detected that before surgery, the following parameters were larger in the PJK group: TK (p<0.001), LL (p=0.005), and PJA (p=0.03) in Lenke type 5 AIS patients. Immediately post-operatively, in the PJK group, the following parameters were higher: TK (p<0.001), LL (p=0.005), and PJA (p<0.001). At the final follow-up, the following parameters were higher in the PJK group: TK (p<0.001), LL (p<0.001), and PJA (p<0.001).The individuals with larger preoperative TK were more susceptible to PJK, and PJA was mainly influenced by the adjacent segments rather than the whole sagittal alignment. Using hooks or claws at UIV should prevent PJK.